UPAYA MENINGKATKAN HASIL BELAJAR IPA SISWA MELALUI METODE PEMBELAJARAN KOOPERATIF TIPE STADSISWA KELAS VA SDN 021 TANJUNG PALAS KECAMATAN DUMAI TIMUR KOTA DUMAI - Sabarina Br. Bangun (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This classroom action research aimed to improve the science learning outcomes of fifth-grade students at SD Negeri 021 Tanjung Palas, Dumai Timur District, Dumai City, through the implementation of the Student Teams Achievement Divisions (STAD) cooperative method. The subjects of the study were 26 students of class V A at SD Negeri 021 Tanjung Palas, Dumai Timur District, Dumai City. The data used in this study included students’ learning outcomes, student activities, learning mastery, and teacher activities. The instruments used consisted of learning instruments, including a syllabus, lesson plans (RPP), and student worksheets (LKS), as well as data collection instruments, including observation sheets for student activities, observation sheets for teacher activities, and test sheets. The results showed that students’ learning mastery before the cycles was 69.7 and had not yet reached mastery, increased in the first cycle to 75.07, which met the mastery criteria, and further increased in the second cycle to 80.9. It can be concluded that the science learning outcomes of fifth-grade students at SD Negeri 021 Tanjung Palas, Dumai Timur District, Dumai City, can be improved through the application of the STAD cooperative learning method.